Leitura crítica de textos da mídia: desnaturalizando discursos hegemônicos em aulas de Língua Portuguesa do Ensino Fundamental II - Camila Emanuele de Oliveira Abreu (2018)
This work proposes an analysis of the strategies of critical reading, among them the workshops of reading of several texts conveyed in the Brazilian media. The activities were developed in Portuguese language classes, in basic education, with an 8th grade class from a municipal public school. The work was divided into three distinct stages: the first stage aimed at diagnosing students' socioeconomic profile and reading interests, considering the consumption habits of printed, television and virtual media. Subsequently, the students participated in reading and journalistic texts, converging with the interests listed in the first stage, in order to launch a reflexive look at the positions adopted by the communication vehicles and also on the social impacts of dissemination and dissemination. passive reception of these statements. The third step consisted in verifying the progress made with the critical reading workshops, through the production of publicity videos and warning of the marketing interests of the texts conveyed in the media, in order to make the public aware of the importance of a critical- reflective of these texts - newspapers, soap operas, advertisements, etc. For that, a channel was created on the Youtube platform, freely accessible by the school community, in which the videos produced by the group were posted. The results obtained proved to be relevant in the field of discursive analysis, since it demonstrated the perception that all linguistic, visual and discursive choices are not random, but driven by ideological interests.